Two-year longitudinal trajectory patterns of albuminuria and subsequent rates of end-stage kidney disease and all-cause death: a nationwide cohort study of biopsy-proven diabetic kidney disease. Issue 1 (12th August 2021) - Yamanouchi, Masayuki; Furuichi, Kengo; Hoshino, Junichi; Toyama, Tadashi; Shimizu, Miho; Yamamura, Yuta; Oshima, Megumi; Kitajima, Shinji; Hara, Akinori; Iwata, Yasunori; Sakai, Norihiko; Oba, Yuki; et al.
Abstract : Introduction: Data on the association between longitudinal trajectory patterns of albuminuria and subsequent end-stage kidney disease (ESKD) and all-cause mortality in diabetic kidney disease (DKD) are sparse. Research design and methods: Drawing on nationally representative data of 329 patients with biopsy-proven DKD and an estimated glomerular filtration rate above 30 mL/min/1.73 m 2 at the time of biopsy, we used joint latent class mixed models to identify different 2-year trajectory patterns of urine albumin to creatinine ratio (UACR) and assessed subsequent rates of competing events: ESKD and all-cause death. Results: A total of three trajectory groups of UACR were identified: 'high-increasing' group (n=254; 77.2%), 'high-decreasing' group (n=24; 7.3%), and 'low-stable' group (n=51; 15.5%). The 'low-stable' group had the most favorable risk profile, including the baseline UACR (median (IQR) UACR (mg/g creatinine): 'low-stable', 109 (50–138); 'high-decreasing', 906 (468–1740); 'high-increasing', 1380 (654–2502)), and had the least subsequent risk of ESKD and all-cause death among the groups. Although there were no differences in baseline characteristics between the 'high-decreasing' group and the 'high-increasing' group, the 'high-decreasing' group had better control over blood pressure, blood glucose, and total cholesterol levels during the first 2 years of follow-up, and the incidence rates of subsequent ESKD and all-cause death were lower in the 'high-decreasing' group compared with the 'high-increasing' group (incidence rate of ESKD (per 1000 person-years): 32.7 vs 77.4, p=0.014; incidence rate of all-cause death (per 1000 person-years): 0.0 vs 25.4, p=0.007). Conclusions: Dynamic changes in albuminuria are associated with subsequent ESKD and all-cause mortality in DKD. Reduction in albuminuria by improving risk profile may decrease the risk of ESKD and all-cause death.